Criminalizing medical negligence: a comparative study between the United States of America and Malaysia / Muhammad Firdaus Bin Adnan ... [et al.] - Adnan, Muhammad Firdaus; Ahmad, Muhammad Syafiq; M.Razali, Ahmad Syahmi; Rasid, Muhammad Amir Syeqal (2011)
The law of torts, through the use of the Neighbour principle and the Foo Fiona's Test has been the only control device for medical negligence cases in Malaysia up until now. Medical negligence which governed by civil system is somehow unable to restrain cases of negligence by medical practitioners from arising day by day. The existence of this standard of care however does not seem to constantly put medical practitioner on the standard required. In moving a step further, we can lift the standard of healthcare and providing justice to the medical negligence victims by criminalizing medical negligence which has been done at United States of America. With the existence of a good and strict deterrence, doctors and other health personnel will use more care and caution when conducting medical procedure on their patients.